The Ontology of The Global Administrative Space Within Transnational Climate Policy - Keith Goldstein; Bruna Rodrigues; Jörgens, H.; Kolleck, N. (ECPR General Conference 2025, 2025)
As the climate crisis intensifies, there is a pressing need to illuminate the conceptual underpinnings of global policy networks. Central to our inquiry is the concept of a Global Administrative Space (GAS), a transnational realm where diverse actors converge to shape global policies. This paper examines the philosophical basis for different GAS network models, hypothetical methods to evaluate them, and empirical studies that at least partially utilized a similar model. Drawing on ten distinct theoretical perspectives, we examine distinct dimensions of policy formation: from the prominence of hierarchical hubs that concentrate resources and decision-making authority (Centralized Network Hypothesis) to the fracturing into clusters (Decentralized Network Hypothesis). Additionally, we highlight cross-cutting factors such as Actor Network Theory, subcultural affiliations, informal “sublime” interactions, and embedded social norms, which mediate the impact of network ties on concrete policy outcomes. Methodologically, our framework lends itself to a variety of approaches, including Qualitative Comparative Analysis, Social Network Analysis, and Path Analysis. We also propose utilizing bibliometrics, ethnography, web scraping, and additional data collection methods for capturing global policy dynamics specific to each hypothetical model. While the examples that we present focus specifically on climate policy, we highlight how the rubric could be utilized towards other topics of global policy research. The aim of the paper is to provide scholars of global administration from a variety of disciplines a versatile toolkit of hypotheses and methods to evaluate global policy development.